SME Upgrading Program : Exploring Initiatives that Combine Market Linkages and Capability Strengthening - World Bank Group (World Bank, Washington, DC, 2020)
This paper examines interventions that seek to address firm-level capabilities and access to markets in an integrated fashion. Examples of such interventions include supplier development programs (linking domestic SMEs in developing countries with large buyers, such as foreign investors that are part of global or regional value chains) and export development efforts (which work with firms beyond purely funding activities to explore and pursue opportunities in foreign markets). These programs aim to assist firms with upgrading, targeted toward the specific market opportunities in the value chains in which they operate or aim to compete.